PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK DI KELAS IV SDN 07 BELAKANG BALOK KOTA BUKITTINGGI - Riyandi, Riyandi; Suarman, Farida; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This background of this research was the student’s result still the low at the forth grade of elementry school Belakang Balok Bukittinggi City. The purpose of this research wass to describe the improvement of student’s learning result at sosial (IPS) lessonn by applying Talking Stick model at the forth grade of elementry school 07 Belakang BKT. Desing of this  research was an action research (PTK) that use qualitative and quantitative approach. Student’s learning outcome 75 on fisrt cycleI increased to 88 0n seconf cycle. Thus on social (IPS) learning by applying the Talking Stick model can improve student’s learning outcomes.  Keywords: Learning Outcomes, IPS, Talking Stick Models